A comparative study of endoscopic versus conventional septoplasty: an analysis of 50 cases - Chandra, Sagar; Baisakhiya, Nitish (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2017)
Background: Nasal obstruction is the most common complaint in ENT practice. Surgical correction of deviated nasal septum has been performed by a variety of techniques of which sub mucous resection and Septoplasty procedures of surgical correction of nasal septum play a prime role in management of patients of nasal obstruction. Nasal endoscope is very useful tool to visualize posterior part of septum and do the surgery more precisely and with less complication as compare to conventional method. The objectives of the study were to compare the outcomes of conventional and endoscopic septoplasty, to evaluate the advantages, disadvantages and complications of both endoscopic and conventional septoplasty Methods: 50 cases (between (Oct. 2014 - March 2016) of deviated nasal septum selected in this prospective study and they were randomly divided equally in 2 groups for endoscopic (A) and conventional (B) septoplasty respectively. Results: The study included 50 cases. Majority of patients in this study were males 84% (n=42) and 16% (n=18) were female. 46% (n=23) patients had DNS to right side and 54% (n=27) patients had left side, anterior deviation (48%). C and S shaped deviations (14%). Spur was present in 22% (n=11) of cases and 10% (n=5) patients presented with thickening. After completing 2 months of follow up 92% (n=23) of group A and 88% (n=22) of group B were relieved from nasal discharge, while nasal obstruction was absent in 96% (n=24) patients of group A and 80% (n= 20) of group B. 4% cases (n=1) in endoscopic septoplasty was having persistent deviated nasal septum and 16% (n=4) patients of conventional septoplasty belong to this group. Conclusions: Endoscopic septoplasty has an obvious edge over the conventional approach due to better illumination which enables to identify the pathology accurately, excise the deviated part of septum precisely and realignment of the cartilage for best results.